Environmental education on public squares: teachers and students discovering the urban environment - Luiz Fernando Rolim de Almeida; Luiz Roberto Hernandes Bicudo; Gilberto Luiz de Azevedo Borges (Revista Ciência em Extensão, 2010)
Environmental Education Proposals can bring solution to environmental problems and minimize the damage caused by the human race. The public square and other public spaces can be used as environmental education activities with teachers and their students from the schools near the square. This research evaluated the participation of students and teachers from elementary schools and encouraged them to see the environment with critical eyes. The history of Botucatu was researched in old newspapers, books and by interviewing history writers from Botucatu. Teachers and students from 4th and 6th grades developed some activities in the square and the results were evaluated based on the statements made by the participants.